Price Stability and Productivity in West Java Potato Farming: Indofood Partnership vs. Traditional Sales - Pratama, Dery Ramdhan (Kadiri University - Faculty of Agriculture, 2025)
This study explores the comparative advantages of Indofood’s contract farming model over traditional potato marketing practices in West Java, Indonesia, focusing on price stability and sustainable production. West Java, the country’s leading potato-producing region, has recently faced declining yields and unstable prices that threaten farmer livelihoods. Indofood’s structured partnership addresses these issues by offering guaranteed pricing, input support, and continuous agronomic assistance. A mixed-methods approach was applied, combining quantitative surveys with qualitative interviews and focus group discussions involving Indofood-affiliated and independent farmers in Garut and Pangalengan. The analysis considered production consistency, income security, crop quality, and farmer perceptions while accounting for external factors such as weather variability and market fluctuations. Findings reveal significant differences between partner and non-partner farmers. Partnership members reported higher yields, more secure prices, and greater income stability, supported by access to Atlantic seed potatoes, fertilizers, and training. These resources reduced pest damage, improved farm management, and minimized market risks. Focus group results showed high satisfaction and trust in Indofood’s contractual commitments, with many farmers benefiting from community development initiatives and eco-friendly practices. Nonetheless, some concerns remain regarding seed availability and buy-back scheduling. The study demonstrates that Indofood’s contract farming model strengthens farmer resilience, enhances productivity, and contributes to rural sustainability. By integrating fixed pricing with farmer capacity building and community support, the model offers a scalable template for agribusiness partnerships in emerging economies seeking to address similar agricultural challenges.